An integer programming model for analysing impacts of different train types on railway line capacity - Yaghini, Masoud; Nikoo, Nariman; Ahadi, Hamid R. (Transport, 2014)
The evaluation of railway line capacity is an important problem, which effects majority of problems in rail transportation planning. The railway capacity is dependent on infrastructure, traffic, and operating parameters. A key factor affecting railway line capacity is the impact of different train types. As the combination of different train types increases, more interference is generated. In this paper, for evaluation of train type interactions on railway line capacity, an integer-programming model for both line and line section is presented. The problem is formulated as a multicommodity network design model on a space-discrete time network. The railway capacity is calculated using data typically available to planners. The inputs of the model are the characteristic of each train type and railway line attributes. The model determines railway capacity based on train type mixes. In addition, this model considers impact of train types on capacity and waiting time. In order to show the features of the model, a case study is implemented in Iran Railways. The capacity tends to increase non-linearly with small incremental changes in parameters. The mixture of train types reduces the railway line capacity. The proposed model can help railway managers for long-term planning. First Published Online: 25 Mar 2014